MEDIA BARU DIGITAL SEBAGAI PERETAS KONTEKS KOMUNIKASI ANTAR PRIBADI DAN KELOMPOK - yudha, reza praditya; irwansyah, irwansyah irwansyah (Islamic Communication Journal, 2018)
Digital media creates a gap in the definition of the communication context created by West & Turner (2010). Situational boundaries are increasingly unclear when in the whole process the number of participants, distance, space, feedback, media functions, and variety of channels are integrated. This study aims to analyze the implications of digital media functions in elaborating interpersonal communication to successfully mobilize groups. The study was conducted by reviewing the literature on new digital media theories. As a result, connectedness occurs as a character of interpersonal communication in digital new media. When these context is elaborated by digital media so that integrating more participants, interaction is not just merely connection anymore, but focuses on shared meaning. At this point the context is shifted into group communication.Â Keywords : new digital media, communication context, interpersonal communication, group communication